Flatwise compression property of hierarchical thermoplastic composite square lattice. (15th February 2019) - Liu, Houchang; Chen, Liming; Du, Bing; Peng, Shiwei; Guo, Yongguang; Zhao, Yang; Chen, Liliang; Zhou, Hao; Li, Weiguo; Liu, Pan
Abstract: Hierarchical lattice structures have many advantages such as lightweight, high specific strength and multifunctional properties. Thermoplastic composite material can offer good ductility and meet the recycling and environmental-friendly requirements. Hierarchical thermoplastic composite square lattices (HTCSLs) were designed and manufactured with interlocking assembly technique. Flatwise compression tests were conducted to investigate the deformation mechanism, energy absorption property, and the influence of structural dimensions. Theoretical and numerical analysis were conducted to predict the deformation process. To reduce the initial peak load and increase the energy absorption before limit load, hierarchical thermoplastic composite sandwich panels (HTCSPs) were designed and manufactured. Different from the complete crushing of brittle structures, HTCSLs showed good ductility and could maintain the shape integrity of the structure after failure. After unloaded, a 67–80% elastic deformation recovery was found. Specific energy absorption of the HTCSLs is comparable to that of aluminium lattice trusses, better than most of other reported lattice structures. After introducing hierarchy, the energy absorption properties of both the HTCSLs and HTCSPs are much superior to the multilayer HolyPan® structures, increased to nearly 5 times. Moreover, on the premise of energy absorption, the initial peak load of the HTCSPs is reduced to the level of the plateau load.